1969
DOI: 10.1111/imj.1969.18.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis and Obesity: The Effect of Weight Reduction

Abstract: SUMMARY In eight obese subjects the initially low level of fibrinolytic activity increased after significant weight reduction. Reduction to a normal weight resulted in normal fibrinolytic activity, which was maintained when an isocaloric diet was resumed. Subsequent weight gain in two subjects caused a return of fibrinolytic activity to its initially low level. Overall, the ultimate level of fibrinolysis achieved was closely related to the degree of obesity. The changes in fibrinolysis appeared to be unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1970
1970
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…This is in contrast to the findings o f several workers [1][2][3][4][5][6][7] who found decreased fibrinolytic activity in overweight individuals. One explanation of this discrepancy may be that the subjects included in the present study were all young (19-24 years of age) and healthy, whereas in the other reported series the age varied between 19-78 years with a mean in the range o f 40-50 years.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to the findings o f several workers [1][2][3][4][5][6][7] who found decreased fibrinolytic activity in overweight individuals. One explanation of this discrepancy may be that the subjects included in the present study were all young (19-24 years of age) and healthy, whereas in the other reported series the age varied between 19-78 years with a mean in the range o f 40-50 years.…”
Section: Discussioncontrasting
confidence: 99%
“…Weight reduction is known to be associated with a rise in fibrinolytic activity (Grace, 1969), and lest this might be responsible for changes in plasma fibrinolytic activity, the patients' weights were followed. No signscant difference was found between Groups A, B and C either before or during the first 6 mth of treatment and no patient described loss of appetite while on treatment with phenformin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an increase in fibrinolytic activity occurs during weight reduction in the obese [4,13], and that short-term negative calorie balance also causes the fibrinolytic activity to increase in persons of normal body build [13], We report a study on the fibrinolytic enzyme system in patients with anorexia nervosa to determine whether chronic negative calorie balance is associated with a sustained increase in fibrinolytic activity and whether it results in alterations in the other components of the fibrinolytic system. …”
mentioning
confidence: 95%